Multifactorial day hospital intervention to reduce falls in high risk older people in primary care: a multi-centre randomised controlled trial [ISRCTN46584556] - Masud, Tahir; Coupland, Carol; Drummond, Avril E.R.; Gladman, John R.F.; Kendrick, Denise; Sach, Tracey; Harwood, Rowan H.; Kumar, Pradeep; Morris, Rob; Taylor, Rachael; Youde, Jane; Conroy, Simon (BioMed Central, 2006)
Falls in older people are a major public health concern in terms of morbidity, mortality and cost. Previous studies suggest that multifactorial interventions can reduce falls, and many geriatric day hospitals are now offering falls intervention programmes. However, no studies have investigated whether these programmes, based in the day hospital are effective, nor whether they can be successfully applied to high-risk older people screened in primary care.